Virtual bronchoscopic navigation and endobronchial ultrasound with a guide sheath without fluoroscopy for diagnosing peripheral pulmonary lesions with a bronchus leading to or adjacent to the lesion: A randomized non‐inferiority trial. Issue 4 (10th November 2022) - Zheng, Xiaoxuan; Zhong, Changhao; Xie, Fangfang; Li, Shiyue; Wang, Guiqi; Zhang, Lei; Sun, Jiayuan
Abstract: Background and Objective: Transbronchial sampling of peripheral pulmonary lesions (PPLs) is routinely performed under fluoroscopy. However, advanced ancillary techniques have become available, such as virtual bronchoscopic navigation (VBN) and radial endobronchial ultrasound with a guide sheath (rEBUS‐GS). This study was performed to determine whether the diagnostic utility of VBN and rEBUS with a GS is similar with or without fluoroscopy. Methods: This multicenter non‐inferiority trial randomized patients to a VBN‐rEBUS‐GS with or without fluoroscopy group at three centres. The primary endpoint was the diagnostic yield. The secondary endpoints were the time for rEBUS, GS, and the total operation. Complications were also recorded. Results: Four hundred and ninety‐six subjects were assessed and 426 subjects were included in the analysis (212 in non‐fluoroscopy‐guided‐group and 214 in fluoroscopy‐guided‐group). The diagnostic yield in the non‐fluoroscopy‐guided‐group (84.0%) was not inferior to that in the fluoroscopy‐guided‐group (84.6%), with a diagnostic difference of −0.6% (95% CI: −6.4%, 5.2%). Multivariable analysis confirmed that bronchus sign and lesion nature were valuable diagnostic predictors in non‐fluoroscopy‐guided‐group. The non‐fluoroscopy‐guided‐group had shorter rEBUS, GS, and total operation time. No severe complications occurred in either group. Conclusion: Transbronchial diagnosis of PPLs suspicious of malignancy and presence of a bronchus leading to or adjacent to lesions using VBN‐rEBUS‐GS without fluoroscopy is a safe and effective method that is non‐inferior to VBN‐rEBUS‐GS with fluoroscopy. Bronchus leading to lesions and malignant nature are associated with high diagnostic yield in VBN‐rEBUS‐GS without fluoroscopy for the diagnosis of PPLs. Abstract : The randomized multicenter clinical trial evaluated that transbronchial diagnosis of PPLs suspicious of malignancy and presence of a bronchus leading to or adjacent to lesions using VBN‐rEBUS‐GS without fluoroscopy was a safe and effective method and it was non‐inferior to VBN‐rEBUS‐GS with fluoroscopy.